Kekerabatan Bahasa Batak Toba di Kecamatan Onan Ganjang Kabupaten Humbang Hasundutan Provinsi Sumatera Utara dan Bahasa Minangkabau di Kecamatan Lubuk Begalung Kota Padang Provinsi Sumatera Barat - Debora Chatarina Sihombing; Agustina Agustina (Persona: Kajian Bahasa dan Sastra, 2023)
Research is conducted with the aim to (a) determine the level of degrees of the two languages studied, (b) determine the separation distance between the two languages studied, and (c) find out the sound correspondenes between the language studied. This type of research is qualitative and quantitative research in the field of Comparative Historical Linguistic. The research entity is the Toba Batak Language in Onan Ganjang District, Humbang Hasundutan Regency, North Sumatera Province and the Minangkabau language in Lubuk Begalung District, Padang City, West Sumatera Province. The data for this research are spoken and written which are guide by the Morris Swadeshvocabulary list and the cultural voabulari lists of the two language studied. Based on existing alculations and research data, a related vocabulary was found between the Toba Batak language in Onan Ganjang District, Humbang Hasundutan Regency, North Sumatera Province and the Minangkabau language in Lubuk Begalung District, Padang City, West Sumatera Province, a total of 99 related words (cognates) and 401 words (not cognates). So, the percentage level of kinship between the two language is 18%. Next, the glotohronolgy calculation show that separation of the two language is from 1928 BC, starting from 2023. Based on the 500 vocabularies found, there were sound correspondences consisting of 43 sound/phoneme replacement vocabularies, 1 sound/phoneme reduction vocabulary, and 10 sound addition vocabularies/phoneme.